Cell differentiation, aging, and death in spatially organized yeast communities: mechanisms and consequences - Palková, Zdena; Váchová, Libuše (Cell death and differentiation, 2025)
Cell death is a natural part of the development of multicellular organisms and is central to their physiological and pathological states. However, the existence of regulated cell death in unicellular microorganisms, including eukaryotic and prokaryotic microbes, has been a topic of debate. One reason for the continued debate is the lack of obvious benefit from cell death in the context of a single cell. However, unicellularity is relative, as most of these microbes dwell in communities of varying complexities, often with complicated spatial organization. In these spatially organized microbial communities, such as yeast and bacterial colonies and biofilms growing on solid surfaces, cells differentiate into specialized types, and the whole community often behaves like a simple multicellular organism. As these communities develop and age, cell death appears to offer benefits to the community as a whole. This review explores the potential roles of cell death in spatially organized communities of yeasts and draws analogies to similar communities of bacteria. The natural dying processes in microbial cell communities are only partially understood and may result from suicidal death genes, (self-)sabotage (without death effectors), or from non-autonomous mechanisms driven by interactions with other differentiated cells. We focus on processes occurring during the stratification of yeast colonies, the formation of the extracellular matrix in biofilms, and discuss potential roles of cell death in shaping the organization, differentiation, and overall physiology of these microbial structures.
Keywords: Saccharomyces cerevisiae; Biofilms; buněčná diferenciace; kvasinky; Cell Differentiation; Cell Death; Yeasts; buněčná smrt; biofilmy